Building better teams 70 tools and techniques for strengthening performance within and across teams - Barner, Robert (Pfeiffer, 2012)
"Over the past 10 years in the field of human and organizational development, the approach to team building has moved from problem solving and conflict management to helping work groups and organizations build a foundation of trust, cooperation, and mutual support. Focusing on collaboration rather than resolving conflict, Creating Collaboration: Tools for Building and Strengthening Team and Organizational Performance offers at fresh approach to team building. It provides proven tools for the most common challenges faced by groups, including establishing trust, gaining goal alignment, building consensus, working virtually and across boundaries, and dealing with setbacks"--